THE INFLUENCE OF TEACHER’S PERSONALITY COMPETENCE ON THE LEARNING INTEREST OF CLASS VI STUDENTS AT SD NEGERI 3 KRASAK PECANGAAN JEPARA (PIONIR: JURNAL PENDIDIKAN, 2024)
The aim of this research is to determine the influence of teacher personality competence on the learning interest of class VI students at SD Negeri 3 Krasak Pecangaan Jepara. This research method uses a quantitative approach with an expost facto type of research. The data collection technique in this research uses questionnaires which are used to measure teachers' personality competencies and students' interest in learning. get results in a simple regression test, get a significance value of 0.004, this value is 4.49, H0 was rejected and Ha was accepted. Then, the coefficient of determination test shows that the correlation value (R) is 0.653, and the coefficient of determination (R Square) is 0.426, which means that the influence of Teacher Personality Competence on Student Learning Interest is 42.6%. With this it can be concluded that the teacher's personality competence has an influence on students' interest in learning.Keywords: Teacher Personality Competence, Interest in Learning.
Keywords: Teacher Personality Competence; Interest In Learning.